Modulation of Memory by Vestibular Lesions and Galvanic Vestibular Stimulation - Smith, Paul; Geddes, Lisa; Baek, Jean-Ha; Darlington, Cynthia; Zheng, Yiwen (Frontiers in Neurology, 2010)
For decades it has been speculated that there is a close association between the vestibular system and spatial memories constructed by areas of the brain such as the hippocampus. While many animal studies have been conducted which support this relationship, only in the last 10 years have detailed quantitative studies been carried out in patients with vestibular disorders. The majority of these studies suggest that complete bilateral vestibular loss results in spatial memory deficits that are not simply due to vestibular reflex dysfunction, while the effects of unilateral vestibular damage are more complex and subtle. Very recently, reports have emerged that sub-threshold, noisy galvanic vestibular stimulation can enhance memory in humans, although this has not been investigated for spatial memory as yet. These studies add to the increasing evidence that suggests a connection between vestibular sensory information and memory in humans.